4 m/100 Gb/s Optical Wireless Communication Based on Far L–Band Injection Locked Quantum-Dash Laser - Muhammad Talal Ali Khan; Mohamed Adel Shemis; Amr Mohamed Ragheb; Maged Abdullah Esmail; Habib Ali Fathallah; Saleh Alshebeili; Mohammed Zahed Mustafa Khan (IEEE Photonics Journal, 2017)
An indoor 100 Gb/s free space optical communication link using an injection locked ∼1621 nm quantum-dash laser has been experimentally demonstrated. The results are achieved using dual-polarization quadrature phase shift keying (DP-QPSK) and coherent detection over a 4 m indoor free space link. The system exhibited a receiver sensitivity of –17.5 dBm to achieve the bit error rate forward error correction (BER FEC) threshold of 3.8 × 10–3. This displays the potential of tunable injection locked far L -band quantum-dash lasers, with less scattering loss compared to C-band counterpart, as promising light sources in both indoor and outdoor future high speed free space optical information and communication technology.